Haptic exploratory interactions in foot reflexology practice from the practitioners' perspectives - Chimeremeze, O.H. (IEEE Computer Society, 2015)
Haptic exploration helps in the assessment of an object's property that includes its shapes and surface material. The interaction has been widely applied in various domains ranging from textile industry to medical field. Despite its importance, the identified haptic exploratory procedures by renowned authors might not be completely applicable in other domains. This paper presents a study that examines the haptic exploratory procedures in foot reflexology domain since the practices promote relaxation and stress relief. The study explored 2 traditional foot reflexology sessions, results were compared with the existing haptic exploratory procedures. The findings indicate new haptic exploratory procedures that are of important benefit to haptic exploration and enhanced the existing haptic exploratory procedure. Â© 2014 IEEE.